Memorandum on the Beveridge Report - Beveridge, William Henry Beveridge, Baron, 1879-1963 (London : Communist Party of Great Britain)
1943-02 1943 1940s 28 pages be appointed by the Crown. The Chairman would be a member of legal profession and would be appointed by the Crown. Two members of the Board would be appointed by the General Council of the Trades Union Congress. A further two members would be appointed by the employers organisation. The remaining two members would be appointed for their special knowledge of medicine and finance respectively. All these would be whole time salaried appointments. Britain would be divided into workmen's compensation areas, for each of which a compensation officer would be appointed by the State. For the same areas a local committee, composed of equal numbers of employers and trade unionists plus an independent chairman who would be a member of the legal profession would be appointed. The Chairman would be a full-time appointment. The other members of the Committee would be paid expenses for their attendance. The procedure under this arrangement is as follows :— The Compensation officer would give a written decision on the claim within 14 days. In the event of the claimant being dissatisfied the matter would be referred to the local committee. There could be an appeal from the decision of the local committee to the Workmen's Compensation Board provided: (1) the appeal is sanctioned by the local committee or (2) is made by a union of which the appellant is a member. "The decisions of the Board would be on the real merits and judgment of the case and would not be bound to follow strict legal precedent." 20 15X/2/103/272